The Recognition And The Enforcement Of Foreign Judgments - Marasinghe, Lakshman (Journal of Malaysian and Comparative Law, 2019)
One of the principal consideration of a conflicts lawyer when advising his client is the basis upon which he proposes to have the judgment he obtains, enforced, in a foreign jurisdictions. Where the plaintiff fails to obtain satisfaction of a judgment in his favour in the country in which the judgment in question was rendered, the question that surfaces next is whether it could be enforced in some other country in which the defendant's assets or he himself may be found. Unless this could be done, the full impact of Private International law as a system of law for the settlement of disputes with a foreign element comes to nought.